Irradiation of solo papaya (Carica papaya L. cultivar Solo) - Mateo, Robeson San Diego; Azanza, Ma. Patricia V. (1998.)
This study used 0.5 kgy low gamma irradiation dose coupled with low temperature storage (10°C) as post-harvest treatments for solo papayas at the rare-ripe, color break stage. The physico-chemical, microbiological and sensory characteristics of the irradiated and non-irradiated solo papaya samples were monitored for a storage period of 21 d at 10°C. The physico-chemical characteristics of both the non-irradiated and treated solo papaya samples were monitored every 3 d during the 21 d storage period. Results showed that the non-irradiated solo papaya samples matured rapidly than the irradiated solo papaya samples, with approximately 9 d difference in maturity. The pH, texture, soluble solids, and titratable acidity results, which are all considered indices of papaya maturity, indicated that the non-irradiated solo papaya samples ripened faster in terms of softening, increased sweetness development and decreased acidity of the pulp. Microbiological analyses results showed that the irradiated slo papaya samples had significantly less total microbial load than the non-irradiated solo papaya samples. The Total Plate Count (TPC) results for the non-irradiated solo papaya samples were significantly greater than the TPC results of the irradiated samples at all sampling times. However, increases in the TPC results for both the non-irradiated and irradiated samples were established during the entire test period. Statistical analysis results were significant at the 5%level of significance. The Yeast and Molds Count (YMC) for both the non-irradiated and the irradiated solo papaya samples had a trend similar to that of the TPC results. The sensory qualities of table ripe solo papayas were compared after 12 and 21 d for the non-irradiated and irradiated solo papaya samples respectively. T-Test for paired difference results showed that the non-irradiated and irradiated solo papaya samples, during the table ripe stage were not significantly different in terms of color, flavor, odor, sweetness, astringency, and texture characteristics. Both the non-irradiated and irradiated samples were highly acceptable during days 12 and 21 respectively.
Thesi (BSFT)--University of the Philippines Diliman
Keywords: Food -- Irradiation; Papaya